Anatomy of the Inferior Mesenteric Artery Evaluated Using 3-Dimensional CT Angiography. Issue 2 (February 2015) - Murono, Koji; Kawai, Kazushige; Kazama, Shinsuke; Ishihara, Soichiro; Yamaguchi, Hironori; Sunami, Eiji; Kitayama, Joji; Watanabe, Toshiaki
<x xml:space="preserve">Abstract</x> BACKGROUND: The branching of the inferior mesenteric artery and vein varies among individuals. Three-dimensional CT angiography is a less invasive modality than traditional angiographic examination to assess the artery and vein. OBJECTIVE: We aimed to demonstrate the clinical applicability of CT angiography by evaluating bifurcations of the inferior mesenteric artery and the positional relationship between the inferior mesenteric artery and vein. DESIGN: This was a prospective observational study of patients undergoing preoperative CT angiography. SETTINGS: This study was conducted at a single tertiary care institution in Japan. PATIENTS: A total of 471 consecutive patients who underwent preoperative CT angiography from April 2012 to December 2013 were prospectively enrolled. MAIN OUTCOME MEASURES: The branching pattern of the inferior mesenteric artery, the positional relationship between the inferior mesenteric artery and vein, and the associations between inferior mesenteric artery length and clinical features were evaluated. RESULTS: The length of the inferior mesenteric artery varied widely, from 10.1 to 82.2 mm. In 41.2% patients, the left colic artery arose independently from the sigmoid artery, and in 44.7% of the patients, the left colic artery and sigmoid artery had a common trunk, whereas the left colic artery did not exist in 5.1%. The left colic artery was located lateral to the inferior mesenteric vein at the level of the origin of the inferior mesenteric artery in 73.0% of the patients. The incidence of a short inferior mesenteric artery was significantly increased in men with high BMIs (75.0%). LIMITATIONS: Three-dimensional reconstruction was performed by the use of a single software, and angiographic examination was not performed. Therefore, accuracy and reliability of the 3-dimensional reconstruction could not be established for each modality. CONCLUSIONS: Using 3-dimensional CT angiography, preoperative understanding of the anatomic vascular variations can be easily obtained, which would help surgeons to safely perform laparoscopic surgery in the left-side colon and rectum.